Spatially Selective Heteronuclear Multiple‐Quantum Coherence Spectroscopy for Biomolecular NMR Studies. Issue 9 (30th April 2014) - Sathyamoorthy, Bharathwaj; Parish, David M.; Montelione, Gaetano T.; Xiao, Rong; Szyperski, Thomas
Abstract Spatially selective heteronuclear multiple‐quantum coherence (SS HMQC) NMR spectroscopy is developed for solution studies of proteins. Due to "time‐staggered" acquisitioning of free induction decays (FIDs) in different slices, SS HMQC allows one to use long delays for longitudinal nuclear spin relaxation at high repetition rates. To also achieve high intrinsic sensitivity, SS HMQC is implemented by combining a single spatially selective 1H excitation pulse with nonselective 1H 180° pulses. High‐quality spectra were obtained within 66 s for a 7.6 kDa uniformly 13C, 15N‐labeled protein, and within 45 and 90 s for, respectively, two proteins with molecular weights of 7.5 and 43 kDa, which were uniformly 2H, 13C, 15N‐labeled, except for having protonated methyl groups of isoleucine, leucine and valine residues.